2021
DOI: 10.1080/21695717.2020.1870823
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical vestibular dysfunction in type 1 diabetes mellitus

Abstract: Objective Metabolic changes that occur in diabetes mellitus (DM) can interfere with the energy supply for the metabolic active inner ear, resulting in vestibular impairments. The purpose of this study was to evaluate the effects of type 1 DM on the vestibular system using a vestibular test battery. Methods Vestibular function of fifteen asymptomatic type 1 DM patients with a mean age of 28 years (SD= 5.80) and 16 healthy controls with a mean age of 26 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…Of these, all but one small case-control study ( N = 16) ( 52 ) found abnormal utricular responses in people with DM. Significantly delayed latency, or a greater number of abnormal latencies, were the most common finding in people with DM compared to controls, and in one study comparing DMPN to DM and controls ( 45 , 48 , 55 , 57 ). Perhaps due to differences in approaches, two studies identified low amplitude responses in people with DM vs. controls ( 48 , 50 ).…”
Section: Human Studiesmentioning
confidence: 97%
See 4 more Smart Citations
“…Of these, all but one small case-control study ( N = 16) ( 52 ) found abnormal utricular responses in people with DM. Significantly delayed latency, or a greater number of abnormal latencies, were the most common finding in people with DM compared to controls, and in one study comparing DMPN to DM and controls ( 45 , 48 , 55 , 57 ). Perhaps due to differences in approaches, two studies identified low amplitude responses in people with DM vs. controls ( 48 , 50 ).…”
Section: Human Studiesmentioning
confidence: 97%
“…Given this chronological distribution and more recent clinical implementation of cervical and ocular vestibular evoked myogenic potential (VEMP) and multi-canal head thrust tests, the horizontal semicircular canal (SCC) was the most frequently assessed vestibular end-organ in people with Type 1 DM. In these studies, some degree of abnormal caloric responses (low frequency) were consistently reported (5/5 studies), 1/3 reported vestibulo-ocular reflex (VOR) abnormalities with higher frequency SCC tests ( 35 , 36 , 39 42 , 55 , 56 ), and 2/2 reported abnormal saccule and/or utricle function ( 44 , 55 ). In contrast, the otolith received more attention than the SCCs, and SCC assessments were across a range of frequencies (low, middle, high; Table 2 ) ( 17 ) in people with Type 2 DM.…”
Section: Human Studiesmentioning
confidence: 98%
See 3 more Smart Citations